COOPERATIVES IN BELGIUM IN THE ERA OF THE CODE OF COMPANIES AND ASSOCIATIONS: CURRENT DYNAMICS AND PROSPECTS FOR TAX LAW AND NON-TAX LAW - Garroy , Sabine (International Journal of Cooperative Law, 2025)
In this paper, we consider the tax treatment of cooperativesin Belgium. To this end, we analyse the connections between tax and non-tax law,an analysis that is essential for understanding the current tax system (de lege lataperspective). In view of these connections, we highlight issues that should imperatively be addressed in the context of a reform of this tax system (de lege ferendaperspective).